THE FUNCTIONAL OUTCOME OF PELVIC BONE FRACTURES IN BLUNT TRAUMA PATIENTS (The Research of Medical Science Review, 2025)
BACKGROUND: Pelvic fractures, stemming from blunt trauma, are a critical area of focus in trauma care. These injuries pose considerable challenges in terms of clinical management and long-term rehabilitation. The intricate anatomy of the pelvis, combined with the risk of associated injuries, underscores the need for an evidence-based approach to treatment. This study provides insights into the factors influencing outcomes. Recent studies have highlighted the complexity of treating these injuries and their impact on patient outcomes. MATERIAL AND METHODS: An observational study enrolled 92 patients presenting with pelvic fractures due to blunt trauma. Participants were selected through non-probability consecutive sampling. Each patient underwent a detailed assessment, including physical examinations and imaging. Management strategies were standardized based on fracture stability and patient status. RESULTS: Analysis of 92 cases revealed a male predominance (66.3%) and a mean patient age of 38.6 years. Lateral compression injuries were the most frequent type (42.4%). Functional outcomes, measured by the Majeed score, highlighted that younger patients achieved better recovery rates, and early mobilization significantly improved outcomes. CONCLUSION: This study reinforces that timely management of pelvic fractures significantly influences recovery. Factors such as age, injury severity, and early mobilization emerged as pivotal determinants of outcomes. Further research is essential to refine treatment protocols.